2008
DOI: 10.1007/s12032-008-9066-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF and microvessel density in patients with multiple myeloma: clinical and prognostic significance

Abstract: The conflicting data are reported on the clinical significance of VEGF deregulation and intensity of angiogenesis in multiple myeloma. The aim of this study was to evaluate the incidence and prognostic significance of VEGF expression and microvessel density (MVD) in multiple myeloma, as well as the relationship of their expression with selected clinical data, histological features, and proliferative activity of myeloma cells. We analyzed bone marrow biopsy specimens obtained from 59 patients with newly diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…It was reported VEGF was responsible for the development, maintenance, and progression of MM by promoting bone marrow angiogenesis [29]. More recently, it was shown that MVD was a poor prognostic factor in multiple myeloma [30]. Our results showed that Notch1 overexpression was associated with increased VEGF expression and MVD.…”
Section: Discussionsupporting
confidence: 62%
“…It was reported VEGF was responsible for the development, maintenance, and progression of MM by promoting bone marrow angiogenesis [29]. More recently, it was shown that MVD was a poor prognostic factor in multiple myeloma [30]. Our results showed that Notch1 overexpression was associated with increased VEGF expression and MVD.…”
Section: Discussionsupporting
confidence: 62%
“…In the previous paper, the population examined was in fact heterogeneous and included MM subjects and patients with breast cancer who were treated with exemestane, capecitabine or radiotherapy. Moreover, it is well known that in MM patients, there is a significant correlation between angiogenesis and the extent of bone marrow infiltration or proliferative activity, and the different amounts of CECs could reflect a different biological potency of a malignant clone [22,23]. Ria et al [24 ]pointed out that microenvironmental factors (such as hypoxia, inflammation, expression of multiple cytokines and growth factors) regulating tumor-associated blood vessels may induce changes in the proliferation and apoptotic potential even in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…owever, despite a statistically significant relationship between EGF expression and the S, expression of EGF was not considered to be an independent prognostic factor in a past study among PCM patients 8 . Also no significant di erence was reported between EGF-positive and EGF-negative patients with PCM in terms of overall survival in another study 24 . Bone marrow M D was not found to be significantly correlated with S both at diagnosis and prior to transplant 3 and no correlation was noted between baseline bone marrow M D and PFS and S in PCM patients 25 .…”
Section: Discussionmentioning
confidence: 86%